Effect of roasting and microwave pre-treatments of Nigella sativa L. seeds on lipase activity and the quality of the oil. (15th February 2019) - Mazaheri, Yeganeh; Torbati, Mohammadali; Azadmard-Damirchi, Sodeif; Savage, Geoffrey P.
Highlights: Black seed oil has attracted much attention recently. Thermal pre-treatments and moistening can affect black seed oil quality. Microwaving and roasting time significantly affected oil quality. Microwave pre-treatment was more effective than conventional roasting. Reducing lipase activity by pre-treatments has a positive effect on oil quality. Abstract: The present research studied the thermal pre-treatment of non-soaked and soaked black seed (BS) by microwave radiation (1–3.5 min) in comparison with conventional roasting (2–8 min, 180 °C). As BS was treated for a longer time, a significant increase ( p  < 0.05) was observed in total chlorophylls, carotenoids and phenolic contents in the extracted oils. The oils obtained from the soaked seeds (to 8%) had significantly higher oil quality properties. The optimum extraction conditions were: irradiation time of 3.5 min and BS moisture content of 8%, which resulted in an extraction yield of 35.76%, 10643.730 caffeic acid equivalents/100 g, PV of 9.63 meq O2 /kg and 18.88 h of Rancimat oxidative stability. The microwave pre-treatment was more effective than conventional roasting in reducing lipase activity. Based on the results obtained, it was advisable to treat BS with microwaves and soak them before extracting the oil in a cold press at room temperature.